Supplemental Cardioplegia Immediately before Graft Implantation may Improve Early Post-Transplantation Outcome - Tevaearai Stahel, Hendrik T.; Unger, Darja; Schmidli, Juerg; Gahl, Brigitta; Englberger, Lars; Kadner, Alexander; Eberle, Balthasar; Mohacsi, Paul; Carrel, Thierry P. (Frontiers in Surgery, 2014)
Background: Preservation of cardiac grafts for transplantation is not standardized and most centers use a single administration of crystalloid solution at the time of harvesting. We investigated possible benefits of an additional dose of cardioplegia dispensed immediately before implantation. Methods: Consecutive adult cardiac transplantations (2005-2012) were reviewed. Hearts were harvested following a standard protocol (Celsior 2L, 4-8oC). In 2008, 100mL crystalloid cardioplegic solution was added and administered immediately before implantation. Univariate and logistic regression analyses were used to investigate risk factors for post-operative graft failure and mid-term outcome. Results: A total of 81 patients, 44 standard (“Cardio -”) versus 37 with additional cardioplegia (“Cardio +”) were analyzed. Recipients and donors were comparable in both groups. Cardio + patients demonstrated a reduced need for defibrillation (24% vs. 48%, p=0.03), post-operative ratio of CK-MB/CK (10.1±3.9% vs. 13.3±4.2%, p=0.001), intubation time (2.0±1.6 vs. 7.2±11.5 days, p=0.05) and ICU stay (3.9±2.1 vs. 8.5±7.8 days, p=0.001). Actuarial survival was reduced when graft ischemic time was >180 minutes in Cardio – but not in Cardio + patients (p=0.033). Organ ischemic time >180 minutes (OR:5.48, CI:1.08-27.75), donor female gender (OR:5.84, CI:1.13-33.01) and recipient/donor age >60 (OR:6.33, CI:0.86-46.75), but not the additional cardioplegia nor the observation period appeared independent predictors of post-operative acute graft failure. Conclusion: An additional dose of cardioplegia administered immediately before implantation may be a simple way to improve early and late outcome of cardiac transplantation, especially in situations of prolonged graft ischemia. A large, ideally multicentric, randomized study is desirable to verify this preliminary observation.